Amylase-Dependent Regulation of Glucose Metabolism and Insulin/Glucagon Secretion in the Streptozotocin-Induced Diabetic Pig Model and in a Rat Pancreatic Beta-Cell Line, BRIN-BD11 - Kateryna Pierzynowska; Stina Oredsson; Stefan Pierzynowski (Journal of Diabetes Research)
The current study was aimed at highlighting the role of blood pancreatic amylase in the regulation of glucose homeostasis and insulin secretion in a porcine model of streptozotocin- (STZ-) induced diabetes and in a rat pancreatic beta-cell line, BRIN-BD11. Blood glucose, plasma insulin, and glucagon levels were measured following a duodenal glucose tolerance test (IDGTT), in four pigs with STZ-induced type 2 diabetes (T2D pigs) and in four pigs with STZ-induced type 1 diabetes (T1D pigs). Four intact pigs were used as the control group. The effect of amylase supplementation on both acute and chronic insulin secretion was determined in a BRIN-BD11 cell line. The amylase infusion had no effect on the glucose utilization curve or glucagon levels in the healthy pigs. However, a significant lowering of insulin release was observed in healthy pigs treated with amylase. In the T2D pigs, the glucose utilization curve was significantly lowered in the presence of amylase, while the insulin response curve remained unchanged. Amylase also significantly increased glucagon release during the IDGTT in the T2D and T1D pigs, by between 2- and 4-fold. Amylase did not affect the glucose utilization curve in the T1D pigs. Amylase supplementation significantly decreased both acute and chronic insulin secretion in the BRIN-BD11 cells. These data confirm our previous observations and demonstrate the participation of pancreatic amylase in glucose absorption/utilization. Moreover, the present study clearly highlights the direct impact of pancreatic blood amylase on insulin secretion from pancreatic beta-cells and its interactions with insulin and glucagon secretion in a porcine model.